Using nutritional quality of forage and faeces for predicting sustainable livestock and game stocking rates at Pniel Estates in Northern Cape, South Africa - Mbatha, Khanyisile R. (Stellenbosch : University of Stellenbosch, 2006)
Thesis (PhD)--University of Stellenbosch, 2010.